Human umbilical cord mesenchymal stem cell-derived small extracellular vesicles ameliorated insulin resistance in type 2 diabetes mellitus rats - Yap, Seng Kar; Tan, Kian Leong; Abd Rahaman, Nor Yasmin; Saulol Hamid, Nur Fazila; Ooi, Der Jiun; Tor, Yin Sim; Daniel Looi, Qi Hao; Li, Kar Stella Tan; How, Chee Wun; Foo, Jhi Biau (Multidisciplinary Digital Publishing Institute, 2022)
Human umbilical cord mesenchymal stem cell-derived small extracellular vesicle (hUC-MSCs-sEVs) therapy has shown promising results to treat diabetes mellitus in preclinical studies. However, the dosage of MSCs-sEVs in animal studies, up to 10 mg/kg, was considered high and may be impractical for future clinical application. This study aims to investigate the efficacy of low-dose hUC-MSCs-sEVs treatment on human skeletal muscle cells (HSkMCs) and type 2 diabetes mellitus (T2DM) rats. Treatment with hUC-MSCs-sEVs up to 100 μg/mL for 48 h showed no significant cytotoxicity. Interestingly, 20 μg/mL of hUC-MSCs-sEVs-treated HSkMCs increased glucose uptake by 80–90% compared to untreated cells. The hUC-MSCs-sEVs treatment at 1 mg/kg improved glucose tolerance in T2DM rats and showed a protective effect on complete blood count. Moreover, an improvement in serum HbA1c was observed in diabetic rats treated with 0.5 and 1 mg/kg of hUC-MSCs-sEVs, and hUC-MSCs. The biochemical tests of hUC-MSCs-sEVs treatment groups showed no significant creatinine changes, elevated alanine aminotransferase (ALT) and alkaline phosphatase (ALP) levels compared to the normal group. Histological analysis revealed that hUC-MSCs-sEVs relieved the structural damage to the pancreas, kidney and liver. The findings suggest that hUC-MSCs-sEVs could ameliorate insulin resistance and exert protective effects on T2DM rats. Therefore, hUC-MSCs-sEVs could serve as a potential therapy for diabetes mellitus.